"Дневные записки" Якова Марковича як джерело до вивчення українського чоловічого одягу ХVІІ-ХVІІІ ст. - Насінник, Ю. (Народна творчість та етнографія, 2005)
Ukrainian Folk clothing is one of the most important elements of the material culture of the folk. Men's clothing of the 17th-18th Centuries is an interesting object for studying social-economic particularities of the society of this era. It contains some features of the East and West European costumes (for instance, Ukrainian Cossack's clothing includes elements of the Russian and Polish nobility). In 1859 the work "Day Notes" written by Yakov Markovych was published. This diary among other useful information contains a lot of descriptions of men's clothing of his time. This publication is a valuable source for the study an average men's life style and gives us a chance to learn more about the society through individuals.